Sprawozdanie z działalności Studenckiego Koła Naukowego Historii Kultury i Edukacji w roku akademickim 2020/2021 - Gotówka, Martyna; Jachnik, Wojciech; Klimek, Daria; Traczyk, Natalia; Taylor, Sarah (Biuletyn Historii Wychowania, 2023)
Sprawozdanie z działalności Studenckiego Koła Naukowego Historii Kultury i Edukacji w roku akademickim 2020/2021